Logistical tools for refugees and undocumented migrants: smartphones and social media in the city of Fès. (1st April 2019) - Ennaji, Moha; Bignami, Filippo
Abstract : This article reports findings from fieldwork and analyses the impact of mobile technologies and social media on increasing migration flows in Morocco, particularly in the city of Fès. The role of smartphones as a means to support the use of maps, global positioning apps and the use of social media like Facebook and WhatsApp have become essential tools for refugees and undocumented migrants. This article focuses on these logistical aspects, intended as constantly changing adaptations between life-forms and interactions with the social, political and economic conditions to which migrants are exposed. Logistics is understood as the nexus between migrants and these various logistical tools, influencing their mobility and identities, as well as modifying the organisation of communities and cities (of provenance, transit and destination).